2021
DOI: 10.1101/2021.02.19.21252117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive County Level Framework to Identify Factors Affecting Hospital Capacity and Predict Future Hospital Demand

Abstract: Background: As of February 19, 2021, our review yielded a small number of studies that investigated high resolution hospitalization demand data from a public health planning perspective. The earlier studies compiled were conducted early in the pandemic and do not include any analysis of the hospitalization trends in the last 3 months when the US experienced a substantial surge in hospitalization and ICU demand. The earlier studies also focused on COVID 19 transmission influence on COVID 19 hospitalization rate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, they do not consider mobile health clinics or temporal features. Similarly, there are several papers that use multiple regression models for demand/utilization prediction of traditional hospitals and healthcare centers using hospitalization rates and ICU beds (Bhowmik and Eluru 2021), radiology volume records (Côté and Smith 2018), surgeries and admissions volume (Khaldi et al 2017), and blood donation records (Drackley et al 2012). However, none of these studies can be directly used or mildly adapted for the task of predicting the demand of mobile clinics.…”
Section: Related Workmentioning
confidence: 99%
“…However, they do not consider mobile health clinics or temporal features. Similarly, there are several papers that use multiple regression models for demand/utilization prediction of traditional hospitals and healthcare centers using hospitalization rates and ICU beds (Bhowmik and Eluru 2021), radiology volume records (Côté and Smith 2018), surgeries and admissions volume (Khaldi et al 2017), and blood donation records (Drackley et al 2012). However, none of these studies can be directly used or mildly adapted for the task of predicting the demand of mobile clinics.…”
Section: Related Workmentioning
confidence: 99%
“…Placio et al ( 40 ) established that for Miami Dade county the COVID-19 infection is associated with economically disadvantaged population and shows no association with racial/ethnic distribution. Bhowmik et al ( 41 ) found a significant association of demographics, mobility, and health indicators with COVID-19 hospitalization and ICU usage. Bhowmik and Eluru ( 41 ) also developed a model framework to evaluate the impact of mobility on transmission rates in the county while accommodating county-specific features.…”
Section: Introductionmentioning
confidence: 99%
“…Bhowmik et al ( 41 ) found a significant association of demographics, mobility, and health indicators with COVID-19 hospitalization and ICU usage. Bhowmik and Eluru ( 41 ) also developed a model framework to evaluate the impact of mobility on transmission rates in the county while accommodating county-specific features. Iyanda et al ( 42 ) established that the case fatality ratio in the rural counties, and in people of color is higher than the national rate highlighting the health disparities in these groups.…”
Section: Introductionmentioning
confidence: 99%